2014
DOI: 10.1177/8755122513500918
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Induced Aseptic Meningitis Associated With Intrathecal Trastuzumab

Abstract: To report a case of drug-induced aseptic meningitis (DIAM) in a patient receiving intrathecal trastuzumab (ITT) for leptomeningeal carcinomatosis (LC) secondary to HER-2/neu positive breast cancer. Case Summary: A 43-year-old female with stage IV breast cancer presented with headache, parasthesias, and aphasia. Brain imaging suggested leptomeningeal enhancement. Adenocarcinoma cells were found on cerebrospinal fluid analysis, and infectious etiologies were excluded. The patient received 30 mg of ITT via Ommaya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 26 publications
(62 reference statements)
0
7
0
6
Order By: Relevance
“…These occurred in 5% of cases [17]. Independently from one another, Freyer et al and Pappa et al reported the occurrence of drug-induced aseptic meningitis, probably induced by trastuzumab [16,21]. Following the diagnosis of drug-induced aseptic meningitis, Freyer et al discontinued treatment with intrathecal trastuzumab in a 43-year-old patient.…”
Section: Trastuzumabmentioning
confidence: 96%
See 2 more Smart Citations
“…These occurred in 5% of cases [17]. Independently from one another, Freyer et al and Pappa et al reported the occurrence of drug-induced aseptic meningitis, probably induced by trastuzumab [16,21]. Following the diagnosis of drug-induced aseptic meningitis, Freyer et al discontinued treatment with intrathecal trastuzumab in a 43-year-old patient.…”
Section: Trastuzumabmentioning
confidence: 96%
“…Vier Studien beschäftigen sich mit der Verwendung von IT Trastuzumab bei HER2-positiven Mammakarzinomen als Primärtumor [15,16,17,21] [15,17]. In der Metaanalyse wurden in 87,9% der Fälle keine schwerwiegenden unerwünschten Ereignisse verzeichnet.…”
Section: Trastuzumabunclassified
See 1 more Smart Citation
“…6 Interestingly, we found another case of drug-induced aseptic meningitis attributed to IT trastuzumab. 7 However, in the previous case, it was decided to stop IT trastuzumab and the patient suffered progressive neurologic decline. 7 Remarkably, both cases have a similar drug-induced aseptic meningitis potentially associated with IT trastuzumab.…”
mentioning
confidence: 99%
“…7 However, in the previous case, it was decided to stop IT trastuzumab and the patient suffered progressive neurologic decline. 7 Remarkably, both cases have a similar drug-induced aseptic meningitis potentially associated with IT trastuzumab. However, we decided to resume the treatment due to the riskbenefit ratio and the lack of other therapeutic alternatives.…”
mentioning
confidence: 99%